2018
DOI: 10.3390/molecules23020409
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical Analysis, Antioxidant and Antimicrobial Activities of Helichrysum arenarium (L.) Moench. and Antennaria dioica (L.) Gaertn. Flowers

Abstract: Antennaria dioica (L.) Gaertn. and Helichrysum arenarium (L.) Moench. are two species of the Asteraceae family, known in Romanian traditional medicine for their diuretic, choleretic, and anti-inflammatory properties. The aim of the present study was to evaluate the phenolic and sterolic composition of flowers from the two species and to assess their antioxidant, antibacterial and antifungal properties. LC-MS analyses were performed on methanolic, ethanolic and 70% v/v ethanolic extracts, before and after acid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
68
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(69 citation statements)
references
References 34 publications
(61 reference statements)
1
68
0
Order By: Relevance
“…They suggested that the extract of Ginkgo biloba protect DNA from oxidation. In many studies, antioxidant and antigenotoxic properties have been reported for plant extracts and phytochemicals (Anter et al 2010, Babota et al 2018, Behrevan et al 2011, Karuna et al 2009, Kaur et al 2010, Phalanisong et al 2018, Quincozes-Santos et al 2010, Sinha et al 2010, Vasconcellos et al 2010, Zandi and Ahmadi 2000. Ribeiro et al (2001) investigated that extract of M. officinalis has got high value phenol compounds.…”
Section: Resultsmentioning
confidence: 99%
“…They suggested that the extract of Ginkgo biloba protect DNA from oxidation. In many studies, antioxidant and antigenotoxic properties have been reported for plant extracts and phytochemicals (Anter et al 2010, Babota et al 2018, Behrevan et al 2011, Karuna et al 2009, Kaur et al 2010, Phalanisong et al 2018, Quincozes-Santos et al 2010, Sinha et al 2010, Vasconcellos et al 2010, Zandi and Ahmadi 2000. Ribeiro et al (2001) investigated that extract of M. officinalis has got high value phenol compounds.…”
Section: Resultsmentioning
confidence: 99%
“…O-alkylation increases the lipophilicity and bioavailability of these natural products. To the best of the authors' knowledge, there are no previous records of these derivatives in H. plicatum, probably because this species was mostly studied for the phenolic content of more polar extracts [4,86,112,113]. Methoxylated flavones were, however, reported in other Helichrysum species, such as H. viscosum var.…”
Section: Phytochemical Profilementioning
confidence: 98%
“…The bioactive compounds obtained from plants have been used as the main resource of natural products recently (Babotă et al, ; Bahadori, Kirkan, & Sarikurkcu, ; Korga et al, ). The herbal products become very popular especially because the uses of synthetic drugs have several concerns (Zengin et al, ).…”
Section: Introductionmentioning
confidence: 99%